Pressure Drop Correlation Covering Dilute to Dense Regimes of Solid Particle-Gas Flow in a Vertical Conveying Pipe - Yazid Bindar; N. A. Sutrisniningrum; D. Santiani (Journal of Engineering and Technological Sciences, 2009)
More  general  correlations  between  pressure  drop  and  gas-solid  flow variables are developed from the present experimental data. The correlation was modeled  for  a  pneumatic  conveying  system  in  a  vertical  pipe.  The  transition boundary  between  dense  and  dilute  regimes  is  constructed  from  the  pressure drop correlations. The gas-solid particle flow variables are quantified by the gas Reynolds  (Nref)  and  the  solid  Froude  (Frp)  numbers.  The  dense  flow  regime  is indicated  by  the  decrease  of  the  pressure  drop  with  the  increase  of  the  gas Reynolds  number.  In  contrary,  the  dilute  regime  exhibits  the  increase  of  the pressure  drop  with  the  gas  Reynolds  number.  The  proposed  correlations  were built at the range of gas Reynolds number f from 360 to 500 and solid Froude number from 0,01 to 0,02.